(untitled) (Medicine Today, 2010)
Oral cancer is the commonest cancer in the South East Asia. Approximately 20-30% suffer from oral caner in out of all cancer patients diagnosed each year in this subcontinent. In Bangladesh the chronic use of betel quid and chewing tobacco in the mouth has been strongly associated with an increased risk for oral cancer. The last two-decade has been enormous advances in our understanding of cancer at molecular level. This review will give a out line of current knowledge of oral cancer, including basic over view of genetic mechanism involving cell regulation and cancer production. It is generally accepted that neoplasm arises from series of genetic alteration that lead to cellular proliferation & differentiation. In this review article, a brief discussion of important gene responsible for oral cancer, role of oncogenic viruses and molecular aspect of oral cancer progression, invasion & metastasis has been described. Key words: Oral Cancer; invasion; molecular concept. DOI: 10.3329/medtoday.v22i1.5605 Medicine Today Vol.22(1) 2010. 38-42